FDG-PET SUV-max values do not correlate with epidermal growth factor receptor mutation status in lung adenocarcinoma - Putora, Paul M.; Früh, Martin; Müller, Joachim (Respirology (Carlton, Vic.), 2013)
Previous reports suggest a correlation between positron emission tomography with fluorodeoxyglucose maximum standardized uptake value (SUVmax) and epidermal growth factor receptor (EGFR) mutation status in lung cancer. We analysed positron emission tomography with fluorodeoxyglucose SUVmax in 14 patients with EGFR mutations, and a control group of 14 subjects with wild‐type EGFR adenocarcinomas. The mean SUV value was 10.7 for EGFR‐mutated adenocarcinomas and 9.9 for wild‐type tumours. There was no correlation between SUV values and EGFR mutation status. Omitting EGFR testing in lung cancers with low SUVmax is not appropriate.